Mass-23 nuclei in astrophysics - Fraser, Paul; Amos, K.; Canton, L.; Karataglidis, S.; Svenne, J.; Van Der Kniff, D. (IOPScience, 2015)
© Published under licence by IOP Publishing Ltd. The formation of mass-23 nuclei by radiative capture is of great interest in astrophysics. A topical problem associated with these isobars is the so-called 22Na puzzle of ONe white dwarf novae, where the abundance of 22Na observed is not as is predicted by current stellar models, indicating there is more to learn about how the distribution of elements in the universe occurred. Another concerns unexplained variations in elements abundance on the surface of aging red giant stars. One method for theoretically studying nuclear scattering is the Multi-Channel Algebraic Scattering (MCAS) formalism. Studies to date have used a simple collective-rotor prescription to model the target states which couple to projectile nucleons. While, in general, the target states considered all belong to the ground state rotor band, for some systems it is necessary to include coupling to states outside of this band. Herein we discuss an extension of MCAS to allow coupling of different strengths between such states and the ground state band. This consideration is essential when studying the scattering of neutrons from 22Ne, a necessary step in studying the mass-23 nuclei mentioned above.